PENGARUH FAKTOR FUNDAMENTAL DAN VOLUME PERDAGANGAN SAHAM TERHADAP HARGA SAHAM SYARIAH 2014 - 2018 - Achmadi Achmadi; Ifayani Haanurat; Andi Rustam (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2020)
This study aims to determine the effect of fundamental factors represented by four variables, namely: Return on Assets (ROA), Debt To Equity Ratio (DER), Current Ratio (CR) and Book Value (BV) as well as stock trading volume (TVA) on prices. Sharia stocks for the 2014-2018 period in companies in the Jakarta Islamic Index (JII) were 30 companies and the cross section data became 15 companies in a row from 2014-2018 using a significance level of α = 5%. This study has a quantitative approach, descriptive and associative types, using multiple linear regression analysis and using SPSS for windows.The regression results in this study indicate that the independent variables ROA, DER and Book Value partially have a significant effect on Islamic stocks. Only the Current Ratio has no significant effect on Islamic stocks. And among these fundamental factors the most dominant influence on Islamic stock prices in JII is Return On Assets (ROA) during the 2014-2018 period. Then the trading volume of shares affects the price of Islamic shares. Keywords: Fundamentals, Stock Trading Volume, Stock Prices